FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA KARYAWAN PADA BANK DANAMON SIMPAN PINJAM - SUDARMIN MANIK; NOVA SYAFRINA (Maqdis: Jurnal Kajian Ekonomi Islam, 2018)
The theme of the article is "economy based on the principles of Islam". The purpose of this study to determine factors that affect the productivity of employees at Bank Danamon Simpan Pinjam Unit Ps. Duri City. The sample in this research is all employees at Bank Danamon Simpan Pinjam Unit Ps. Duri City totaling 30 people. Sampling was conducted using a sample saturated. The data analysis is done by using validity, reliability, normality test, heteroscedasticity, multicollinearity test, autocorrelation test, multiple linear regression, R2 test, F test, t test. The tests are conducted to determine the relationship between the independent variables (independent variables) and dependent variable (dependent variable). The final conclusion of the study on the variables training, mental and physical abilities of employees, the relationship between superiors and subordinates of employee productivity can be seen from Table F value obtained for F (0,05) (26) = 2.975, while F count on the F test is obtained from the data processed by 7.352, meaning F count = 7.352 > 2.975. From the results of the t test that most affect the employees productivity at Bank Danamon Simpan Pinjam Unit Ps. Duri City is the mental and physical abilities of employees with t value 3.060 > 2.05.